The Impact of Financial Risk Management in Succeeding Mergers and Acquisition Final Project - Dimas Akbar Rizkiyawan (Green Publisher Indonesia, 2022)
This study explored ways to manage financial risk and also risk management in a case of merger and acquisitions. The goals of this study is to 1.) To conduct a critical examination of financial risk management in the field of merger and acquisition, which contains assets calculation, financial analysis, market analysis, and project profitability, as well as the connections between these aspects towards the succession of undergoing a merger and acquisition process. 2.) Review the outcomes of the data analysis in order to reach conclusions and suggestions in the context of successability of mergers and acquisitions. The research strategy that is included in this paper are quantitative research and case study. One of the research strategy is by using a method by David S. Clifton & David E Fyfe from “Project Feasibility Analysis” . Another research strategy that will be used in this paper is the Failure Mode and Effects Analysis. The data collected by the researcher will mainly be coming from PT Indo Kaya Energi in a form of archival method, other than that, some secondary sources from articles and journals on the internet will be used in this research. The study demonstrates that the process of merger and acquisitions needs to be carefully examined, the reason behind this is because the researcher needed to analyze not only the financial statement from the company, but also analyze the market, assets and future project forecast cashflow as stated in “Project Feasibility Analysis”